3D digital holographic polarimetry of diffuse optically anisotropic biological tissue object fields - Ushenko, Alexander; Zheng, Jun; Gorsky, Mykhaylo; Dubolazov, Alexander; Ushenko, Yuriy; Soltys, Iryna; Mikirin, Ivan; Chen, Zhebo; Wanchuliak, Oleh; Gordey, Ivan; Jingxian, Cai (Frontiers in Physics, 2023)
The experimental validation of methods for digital holographic 3D layer-by-layer reconstruction of complex amplitude distributions in different phase planes of diffuse biological tissues histological sections microscopic images with subsequent reconstruction of azimuth and ellipticity polarization maps is presented. Polarization dependencies of the integral and layer-by-layer vector structure of the laser object field azimuth and ellipticity distributions in two types of biological layers samples - fibrous myocardium and parenchymal liver - have been investigated. Scenarios and dynamics of changes in the values of statistical moments of the 1st to 4th orders, which characterize the integral and layer-by-layer polarization maps of diffuse biological tissues histological sections microscopic images with different morphological structures, have been determined. Criteria for selecting the polarization components of the object field that are formed by acts of scattering of different multiplicities have been identified. An example of biomedical application in cancer detection of biological tissues is provided.